2022
DOI: 10.1038/s41467-022-31072-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain-wide reconstruction of inhibitory circuits after traumatic brain injury

Abstract: Despite the fundamental importance of understanding the brain’s wiring diagram, our knowledge of how neuronal connectivity is rewired by traumatic brain injury remains remarkably incomplete. Here we use cellular resolution whole-brain imaging to generate brain-wide maps of the input to inhibitory neurons in a mouse model of traumatic brain injury. We find that somatostatin interneurons are converted into hyperconnected hubs in multiple brain regions, with rich local network connections but diminished long-rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…The resulting image volumes simultaneously contain salient information about injury-induced changes in neural circuitry and are aesthetically pleasing (e.g., see Supplemental Movie 3 in their paper). 6 After TBI, SST neurons receive proportionally more local connections, particularly from CA1 pyramidal neurons. Longrange connections are lost, including from the medial entorhinal cortex (ENTm) and the nucleus of the diagonal band (NDB), 2 major sites of distant input cells.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting image volumes simultaneously contain salient information about injury-induced changes in neural circuitry and are aesthetically pleasing (e.g., see Supplemental Movie 3 in their paper). 6 After TBI, SST neurons receive proportionally more local connections, particularly from CA1 pyramidal neurons. Longrange connections are lost, including from the medial entorhinal cortex (ENTm) and the nucleus of the diagonal band (NDB), 2 major sites of distant input cells.…”
Section: Commentarymentioning
confidence: 99%
“…The study by Frankowski et al 6 uses cutting edge techniques to elegantly map the changes in long-range connectivity to somatostatin (SST) interneurons of the dentate gyrus in the controlled cortical impact (CCI) model of TBI. Somatostatin interneurons are one of the largest classes of interneurons in the cortex and influence pyramidal cell spiking via dendritic inhibition.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies to date have lacked the resolution to discern cell type-specific responses [6][7][8] . More recent work has examined the effect of injury on particular neuron types 9,10 . We reasoned that a detailed look at a model of single mild TBI would provide important insight into the nature and extent of neuronal injury immediately following a concussion.…”
Section: Introductionmentioning
confidence: 99%
“…The thalamus is made up of excitatory projection neurons and inhibitory interneurons, while the stratum is made up of medium-spiny neurons and interneurons. A study on Parkinson’s disease reported altered medium spiny neurons [10]. A mouse cci model of TBI study reported a notably lower proportion of inhibitory input neurons after 24 h of injury [11].…”
Section: Introductionmentioning
confidence: 99%